From Revenue to Reliability: Analyzing YouTube as a Money-Making Platform or an Information Source from the Youth’s Perspective - Amina Ashfaq; Muhammad Husnain; Yasir Saleem (Dialogue Social Science Review (DSSR), 2025)
In the advance digitalized world, YouTube has raised as both a money-making platform and widely used for source of information. Although, with the rise of social media journalism has also made a digital shift which has faded the line between credible content and the content created for audience engagement and profit generation. In Pakistan, traditional media has been facing financial crises and political pressures which has led the journalist and independent content creators turn towards YouTube for economic stability. This digital shift in journalism has led to an increase in biased, misleading, and sensationalized content, which is raising concerns about YouTube’s reliability as a source of information. This research examines the perception of young audience about YouTube in Pakistan, whether they consider YouTube as a trustworthy and credible medium for information or consider it as a merely revenue-generating tool. To analyze this, we conducted a survey involving 140 individuals from diverse educational backgrounds, all of whom actively use YouTube. We used the quota sampling method, where the survey was distributed via Google Froms through email invitations and social media platforms, achieving a 100% response rate. The findings of survey confirmed that content creators use emotional interaction, current affairs, and appealing visuals to attract larger audience and gain higher views. Sensational content is a the main source of revenue generation, and YouTube’s policies are perceived as insufficient in combating misinformation and disinformation